Observations concernant l'hibernation de la truite arc-en-ciel (salmo gairdneri irideus gibbons, 1855) en conditions d'expérimentation au littoral roumain de la Mer Noire - Ioniță, Reveica; Ghițescu, Elena; Dănăilă, Eugenia (Cercetări Marine - Recherches Marines, 2026)
The paper presents the results of the experiments on the rainbow trout (Salmo irideus GIBBONS 1855) wintering in marine and fresh water. The variation of the main physicochemical agents of water, the evolution of the basic somatic characteristics and the biochemical and blood content of the trout maintained in both media are pointed out as well.